Dose-Response-Relationship between Number of Laser Burns and IOP Reduction in Cyclophotocoagulation: An Animal Study. (26th June 2014) - Wagenfeld, Lars; Schwarzer, Hendrik; Roessler, Gernot; Klemm, Maren; Skevas, Christos; Richard, Gisbert; Zeitz, Oliver
Abstract : Purpose . The relationship between number of laser burns of cyclophotocoagulation (CPC) and intraocular pressure (IOP) reduction is unknown. This animal model was established to reveal a possible dose-response-relationship between the number of applied laser burns and the IOP lowering effect. Methods . 30 chinchilla bastard rabbits were divided into 5 groups and treated with either 1, 5, 10, 20, or 30 CPC burns, respectively. IOP was followed up for 1 week. IOP reduction of a single 30-burn treatment was compared with a fractionated treatment (three sessions; one week in between; 10 burns/session). Results . IOP reduction increases nonlinearly with the number of CPC burns (max. - 6.1 ± 1.4  mmHg). Fractionated treatment shows similar IOP reduction with less complications and more constant results compared to single session treatment. Conclusions . The study reveals a complex relationship between IOP reduction and the number of CPC burns. Fractionated CPC gives comparable IOP reduction at a higher degree of safety.